Asclepias syriaca L. – svilenica - Popov, Milena (Acta herbologica, 2023)
Asclepias syriaca L. (ASCSY, fam. Apocynaceae) is a weed originating from the northern parts of the central, northeastern and southeastern America, as well as the vicinal areas of Canada. The common milkweed was introduced to Europe at the beginning of the 19th century as the honey, ornamental and fiber/silk plant. Today, it occurs in many countries of the western and central Europe (France, Austria, Czech Republic, Belgium, Germany, Lithuania, Slovakia, Hungary, Poland, Italy, Slovenia, Croatia, Serbia, Bosnia, Romania, Bulgaria and Russia). The first cases of A. syriaca in Serbia were noted in the 1920s. The common milkweed is the most common on the non-agricultural areas, from where it spreads to the surrounding cultivated areas. This perennial species can grow up to 1.2 m and it has plenty of the underground adventitious buds from which it reproduces vegetatively. The spherical umbels are in the axis of the upper leaves, the flowers of which have a pleasant smell and purple to deep purplish pink color. It is a diploid (2n=22), self-pollinating plant, with the hybridization between the species of the genus Asclepias being very rare. One plant can produce 1-6 fruits, with every fruit containing 150-425 seeds. This species prefers fertile, well-drained soils, but also thrives in very dry soils. The optimal development is achieved in moderately light and moderately warm, neutral to slightly alkaline habitats, tolerating the soil pH values of 4-5. The seeds germinate at a temperature of 20-30ºC. Late frosts of -1 to -2ºC destroy young seedlings, while adult plants can survive that temperature. A. syriaca has allelopathic properties and a negative impact towards a number of plants, both with crops (maize, soybean, sunflower and cultivated sorghum) and weeds (Amaranthus retroflexus, Chenopodium album, Lepidium sativum and Ambrosia artemisiifolia). It can affect the seed germination and the development of the crop seedlings, leading to the significant yield reduction when its occurrence is massive. The control measures include: crop rotation, cultivation of competitive crops, mechanical removal of plants along with the roots, while chemical control measures are recommended as a preventive method, using glyphosate and triclopyr on non-agricultural areas to prevent the weeds from entering the fields.